Implementation of Marketing Public Relations at PT Kapitol Era Mas - Safitri, Safira Dwinawati; El-Adawiyah, Sa’diyah (Educationist: Journal of Educational and Cultural Studies, 2023)
The rapid growth of the F&B (Food & Beverage) industry in Indonesia is an opportunity for all existing business people. This is marked by the emergence of various companies in the F&B sector that compete with each other and have their own characteristics. The purpose of this study was to analyze Marketing Public Relations at PT Kapitol Era Mas based on Kotler's theory which includes Publications, Events, Identity, Media, News, Speeches, Public Service Activities, Sponsorship, Press Relations, Product and Brand Publicity. This study uses qualitative methods and data collection techniques are carried out through a combination of triangulation, with qualitative data analysis. The results of this study indicate that the two most important and interrelated tools for achieving success in Marketing Public Relations at PT Kapitol Era Mas are Publications and Events.